Entre primos : d'«O primo João de Brito» a «O Primo Basílio» - Lima, Isabel Pires de (1994)
This article demonstrates that there are close genetic relations between the ms. O Primo Joao de Brito and the novel O Primo Basilio by Eca de Queiros; although much shorter than the novel, the ms. offers a plot and character development and a use of narrative technique which allow us to determine its genetic proximity to O Primo Basilio: we are thereby given insights into the workings of its author.